Nanotechnology for the regeneration of hard and soft tissues - Webster, Thomas J. (World Scientific, 2007)
The future growth and development of Asia - the most dynamic economic region in the world today - will have important implications for the rest of the global economy. This book offers a futuristic perspective of a wide array of developmental challenges and opportunities facing Asian economies over the next two decades. The future is approached from several different developmental paradigms including technological change and innovation, regional cooperation within Asia and between Asia and the West, poverty reduction, ethics and corruption, and environmental challenges. Future prospects for the two giant economies of China and India are also explored. By offering a comprehensive look at the medium-term future of Asia from such a wide range of different viewpoints, this fascinating book will interest economists, social scientists, politicians, international investment managers and the general public alike.